Influencia de los medios de comunicación en la modalidad virtual en el aprendizaje de los estudiantes de la Carrera de Comunicación Social Extensión Quevedo, año 2021 - Vergara Loor, Lilibeth Gisella (2021)
Nowadays, the new information and communication technologies offer new diversities of means and resources to contribute to teaching, however, the available technology is not the factor that should determine the new models, procedures, or didactic strategies. The creation of a new virtual learning environment inspires in the best pedagogy theories as an educational technological tool are of great help due to its accessibility in any technical or scientific área, it promotes a new competitive and efficient learning highlighting that it is innovated with an inclusive process, motivating and significant, since the most common change is made to the use of a multimedia, interactive and applicative language using different modalities of synchronous activities blogs, maps, conceptual and online time lines. Virtual communication media have also been presented in educational institutions in Ecuador, becoming an aid to tools and advances in technology and communication, one of the fields that is taking advantage of is education, since the internet is a effective means of guaranteeing communication, interaction and the sending of information.